The pain of chronic pancreatitis: a persistent clinical challenge - Goulden, Michael R (Br J Pain, 2013)
The pain of chronic pancreatitis represents a major challenge to those working in the field, including pain specialists, gastroenterologists and surgeons. This article describes the different aetiologies of chronic pancreatitis and lists the models for the pathogenesis of pain, including novel ideas such as the role of the immune system in the modulation of pain. The patient profile in chronic pancreatitis is discussed along with the social impact of the disease in relation to alcohol misuse. The range of treatment strategies including medical, endoscopic and surgical approaches are evaluated. Common analgesic regimes and their limitations are reviewed. The pain of chronic pancreatitis remains refractory to effective treatment in many cases and further study and understanding of the underlying pathophysiology are required.